Experiences of family carers of older people with mental health problems in the acute general hospital: a qualitative study - Clissett, Philip; Porock, Davina; Harwood, Rowan H.; Gladman, John R.F. (John Wiley & Sons, 2013)
Aims To explore the experiences of family carers of people with cognitive impairment during admission to hospital.